The Concept of Tabayyun in Islamic Education as an Effort to Counter Hoaxes Among Students - Rahma Asyifa; Rosdialena (Konsultan Jurnal Ilmiah Indonesia, 2026)
The development of digital technology and social media allows information to spread instantly, but it also increases the risk of false information or hoaxes affecting young people, particularly students. Islamic education offers the principle of tabayyun, which involves verifying the accuracy of information before dissemination, as an effective strategy to address this challenge. This study examines the implementation of tabayyun in Islamic education and its role in enhancing digital literacy and student character. Findings indicate that tabayyun fosters critical thinking, ethical awareness, and responsibility in handling information, producing students who are digitally literate, responsible, and morally grounded in accordance with Islamic values.